Endometrial carcinosarcoma presenting with a solitary breast metastasis − A rare case report - Inês Taborda Leal; Maria Inês Barradas; Gonçalo Freitas; Filipa Castro Coelho; Filipa Santos; Mónica Cardoso; Maria Ana Serrado; Hugo Gaspar (Gynecologic Oncology Reports)
Background: Endometrial carcinosarcoma (ECS) is a rare and highly aggressive malignancy, accounting for approximately 5% of all uterine cancers. While peritoneal seeding and pulmonary metastases are relatively common, breast involvement is exceedingly rare, with only a few cases reported in the literature, primarily involving the serous or clear cell subtypes and typically associated with widespread metastatic disease. To the best of our knowledge, this is the second documented case of a primary ECS metastasizing to the breast, and the first presenting as a solitary breast mass. Case Report: A 68-year-old woman presented to the emergency department with one week history of postmenopausal abnormal uterine bleeding. Endometrial biopsy confirmed the diagnosis of ECS. Staging thoracoabdominal computed tomography (CT) revealed a solitary 11 mm mass in the lower outer quadrant of the left breast, accompanied by two ipsilateral axillary lymph nodes, but otherwise no signs of distant metastases, additional lymphadenopathies, or peritoneal implants were described. Findings on abdominal and pelvic magnetic resonance imaging (MRI) were concordant with CT, demonstrating no suspicious lymphadenopathies or signs of distant metastatic disease. Breast biopsy revealed a papillary carcinoma with CERB2 positivity. The patient underwent total hysterectomy, bilateral salpingo-oophorectomy, omentectomy, pelvic and lombo-aortic lymphadenectomy, as well as left breast lumpectomy and axillary lymphadenectomy. Complete cytoreductive surgery was performed with no macroscopic residual disease. Final pathology confirmed the breast lesioń metastatic origin. Conclusion: This case holds clinical significance as it underscores the necessity of considering a broad differential diagnosis when encountering uncommon or atypical presentations, particularly in high-grade malignancies such as ECS.